Drivers of the rare persistence of sea ice in the western Chukchi Sea in summer 2024 - Jiaxing Gong; Lijuan Song; Xi Zhao; Annette Rinke; Xiaoyu Wang; Yifan Wu; Bo Li; Xiao Cheng (Environmental Research Letters)
During the 2024 Arctic summer, an unexpected sea ice patch (∼100 000 km ^2 ) survived in the western Chukchi Sea, an event that has not occurred in the past 20 years. Combining satellite data, PIOMAS model, and ERA5 reanalysis data, we analyze this anomaly’s evolution and its dynamic and thermodynamic drivers in the 2000–2024 series. The analysis reveals that July–August are key months; ice concentration and thickness during this time determines the fate of the sea ice survival in September. Before July 2024, sea ice near Wrangel Island has experienced rapid and sustained thickening, with its distribution closely resembling the levels observed in 2000 and 2001 (the only other summers with ice survival). Persistent northerly winds east of Wrangel Island during the melt season contributed to sea ice thickening and played a crucial role in its survival. At the same time, a cooler-than-normal air temperature near Wrangel Island supported the stable presence of sea ice in this region. The study underscores that the ‘New Arctic’ conditions, namely thinning and increasingly mobile sea ice, raise the likelihood of unpredictable events of both unexpected sea ice survival and sudden loss.